The Kostënki 18 child burial and the cultural and funerary landscape of Mid Upper Palaeolithic European Russia. (6th December 2017) - Reynolds, Natasha; Dinnis, Rob; Bessudnov, Alexander A.; Devièse, Thibaut; Higham, Thomas
Abstract: Abstract : Palaeolithic burials are few and far between, and establishing their chronology is crucial to gaining a broader understanding of the period. A new programme of radiocarbon dating has provided a revised age estimate for the Palaeolithic burial at Kostënki 18 in European Russia (west of the Urals). This study reviews the need for redating the remains, and contextualises the age of the burial in relation to other Upper Palaeolithic funerary sites in Europe and Russia. The new date, obtained using a method that avoided the problems associated with previous samples conditioned with glue or other preservatives, is older than previous estimates, confirming Kostënki 18 as the only plausibly Gravettian burial known in Russia.